(untitled) (Pravaha, 2024)
This paper aims to analyze the impact of demographic categories on clothing purchases in terms of formal and informal wear. This research employed solely primary sources of data. A structured questionnaire was used to collect information on consumer demographics that affect clothing purchasing decisions. A total of 180 customers were approached in different shopping malls and supermarkets. Of which 159 customers have participated in this research. For data analysis, t-tests and one-way analysis of variance (ANOVA) are employed. The findings indicate that age has no apparent effect on preferences for casual clothes. The findings are also noteworthy, suggesting that formal clothing choices vary with age. Gender is one of the important demographic factors that affect purchase decisions. The findings indicate that gender matters in formal as well as informal clothes. Income also matters in making purchase decisions. The results suggest that income levels influence the affordability and brand preferences for casual wear. They also show that income affects the willingness to spend on formal wear, with higher-income individuals possibly favoring premium brands or bespoke tailoring. Regarding the education level, significant differences were found for casual wear and formal wear. It implies that purchasing preferences are influenced by education level both generally and in specific categories. Occupation is also one of the key factors that affect the buying decisions of individuals. Results show that occupation strongly impacts purchasing decisions across all categories. These results give companies important information about how to target particular demographic groups with their products and marketing tactics, increasing customer happiness and market efficacy. Companies can utilize these insights to position their brands to appeal to a variety of consumer segments, design product lines tailored to particular demographics, and launch focused marketing efforts.